Vulnerable adults in police custody. Issue 1 (20th November 2019) - Cummins, Ian
Abstract : Purpose: The purpose of this paper is to discuss the recent National Appropriate Adult Network (NAAN) report on the role of the appropriate adult. Design/methodology/approach: This paper is based on the NAAN report and a review of relevant policy and research literature. Findings: There to Help 2 highlights that there are still significant gaps in the provision of appropriate adult schemes across England and Wales. These gaps potentially place vulnerable adults at increased risk. Originality/value: This paper is a review of recent research.